Cranial deformation and torticollis of an early feudal burial from Byurakn, Armenia - Khudaverdyan, Anahit Yu. (Acta Biologica Szegediensis, 2012)
The deformities described in this study involved both the skull contour and the cranial base. The custom of deliberate ring deformation of a head was known in the Early Feudal population of the Armenia. The individual had a rhomboid cranial shape. The deformity appeared on the calvarium and cranial base in an early period of life. The calvarial and endocranial base morphology is similar to deformational plagiocephaly (i.e., nonsynostotic plagiocephaly) of patients with associated torticollis. This is the first documented case of torticollis in Armenia.